Development of Virtual Reality Application for Oral and Dental Health Promotion on Early Childhood - Mira Sri Gumilar; Muliadi Muliadi; Warsono Warsono (Jurnal Kesehatan Gigi, 2022)
Oral health  is a condition that cannot be separated from the life of a child because poor of dental health will affect the other bodies. Education of oral health can improving oral health status, because the good education will be improved an effort to maintenance oral health. Improving health knowledge for early childhood can optimizing health promotion because the information will adhere effectively for them. It is important to develop appropriate media for health education in early childhood so the goals of health promotion can be achieved. This study was aim to develop oral health promotion media using virtual reality and to obtain the effectifeness of that media.This study was consist of development research and experimental research that develop virtual reality media and obtain the effectiveness of that media for improving oral health knowledge. This study conducted at SD Negeri 150/IV Jambi City. The stages of development research was done based on the ADDIE method. The method of experimental research was quasi experimental. Validation by expert was involved six expert that covering about design and material. There were eighty eight students to be subjects of this study, fourty for development research and fourty eight for experimental research. The data collected in this study were in the form of qualitative data and quantitative data. The study shown that virtual reality media was decent to use for oral health promotion and it was proven can improving oral health knowledge.